(untitled) (Vietnam Journal of Community Medicine, 2022)
Chronic kidney failure is a complex disease that affects both physically and mentally.To evaluate the main factor of mental health, specifically depression, we conducted a study to evaluate the prevalence of depression and its related factorsin hemodialysis patients at Nguyen Tri Phuong hospital in 2021. A cross-sectional study was conducted from February 2021 to June 2021 on 221 hemodialysis patients at Nguyen Tri Phuong hospital. The prevalence of depression was 13.1%. There was an association between the complication in dialysis and depression (p<0.001). Physicians should notice about mental aspects of patients to ensure the quality of treatment.